Theoretical calculation of positron affinities of solute clusters in aluminum alloys. (January 2016) - Mizuno, Masataka; Araki, Hideki; Shirai, Yasuharu
Abstract: We have performed theoretical calculations of positron states for solute clusters in aluminum alloys to estimate the positron affinity of solute clusters. Positron states of solute clusters in aluminum alloys were calculated under the electronic structures obtained by first- principles molecular orbital calculations using Al158-X13 clusters. We defined the positron affinity of the solute clusters by the difference in the lowest potential sensed by positrons between the solute clusters and Al bulk. With increasing atomic number of 3d metals, the annihilation fraction of the solute clusters rapidly increases at Mn and shows a maximum at Ni. A similar trend is observed for 4d metals. The localization of positron at the solute clusters mainly arises from charge transfer from Al matrix to solute clusters. The positron affinity defined in this work well represents the localization of positron at the solute clusters in aluminum alloys.